Reproductive Costs Increase With Longer Extreme Heat Events in Collembola - Anouk Gremion; Madhav P. Thakur; Gerard Martínez‐De León (Ecology and Evolution)
ABSTRACT Temperature regimes are changing at an unprecedented rate, leading to more intense, frequent, and prolonged extreme heat events. These conditions can undermine the performance of organisms during and after extreme events. Yet, our understanding of how different durations of extreme heat events impact the reproductive traits of soil invertebrates is limited. Here, we experimentally tested how exposure to extreme heat (30°C–26°C, day–night) affects the reproductive recovery of two Collembola species, Folsomia candida (parthenogenetic) and Proisotoma minuta (sexually reproducing), originally reared for several generations at two different source temperatures (15°C and 20°C). We exposed these collembolans to extreme heat events of varying durations (0, 2, 4 or 8 days), and allowed them to recover for 2 days at their respective source temperatures. We then examined how reproductive traits (offspring production and egg sizes) were affected by previous exposure to extreme heat of varying duration. We predicted that prolonged heat events would have greater impacts on the reproductive traits of both Collembola species, particularly for collembolans raised in colder environments (due to lower acclimation to warming) and in traits related to offspring viability (due to their higher thermal sensitivity). Our results show that offspring production—number of eggs and hatchlings—declined with longer exposure to extreme heat in both species. Collembolans raised in the warmer environment had a steeper reduction in the number of eggs with longer exposure to heat, whereas those reared in the colder environment showed more marked reductions in the number of hatchlings (with declines of up to 99% in cold and 49% in warm rearing environments in F. candida), indicating heat‐induced reductions in egg viability. Overall, our results demonstrate that longer exposure to extreme heat reduces the reproductive success of collembolans, with larger fitness consequences for those from colder environments.